The Gains From International Monetary Cooperation Revisited - Tchakarov, Ivan (IMF Working Papers; Working Paper, 2004)
This paper examines the issue of whether countries can improve their welfare by coordinating macroeconomic policies. The main purpose is to compute the gains from international monetary cooperation as the difference between the steady state consumption levels associated with the Nash and the cooperative outcomes of the game in which monetary authorities pursue active monetary policy. A numerical second-order approximation makes the solution of the model possible. Contrary to Obstfeld and Rogoff (2002), who claim that the gains from international cooperation in monetary policy are negligible, the paper finds that they could be very significant and reach as high as 2.2 percent of steady state consumption. This suggests that individual countries could experience significant welfare losses if they concentrate only on domestic stabilization policies.